Przemoc wobec kobiet i kobieca agresja w kontekście ról płciowych i mylnego uznania („misrecognition”) - Dutka, Joanna (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2014)
This article seeks to examine basic patterns of violence against women, myths surrounding those mechanisms as well as situations, in which women are perpetrators of the violence. The purpose is to draw attention to the fact, that violence affects women’s lives in social, economical and political areas, regardless if said violence happens in the public sphere or private sphere as well as how omission and lack of acknowledgement and deformation of female experience with violence affects women’s social standing.
Violence against women and women’s aggression in light of gender roles and problems of misrecognistion
Keywords: domestic violence; sexual abuse; violence against women; female aggression; recognition; gender norms; public space; private space